1998
DOI: 10.1039/a706647c
|View full text |Cite
|
Sign up to set email alerts
|

Chemiluminescence determination of naltrexone based on potassium permanganate oxidation

Abstract: A rapid method by chemiluminescence is described for the determination of naltrexone. The method is based on the chemiluminescence reaction with potassium permanganate in sulfuric acid medium. The optimum conditions for the chemiluminescence emission were investigated. With the integrated chemiluminescence intensity for 10 s after KMnO4 injection as a quantitative parameter, naltrexone can be determined over the concentration range 50-1000 ng ml-1 with a detection limit of 2.5 nm ml-1 and with a RSD (n = 10) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…The effect of KMnO 4 concentration upon the CL intensity was examined in the range 0.025-0.35 mmol/L. The results showed that the signal/blank ratio of CL emission reached a maximum value when the concentration of KMnO 4 was 0.05 mmol/L, and higher concentrations of KMnO 4 resulted in a decrease of the CL emission intensity, owing to the KMnO 4 absorbing the emitted light (26,27). Therefore, 0.05 mmol/L KMnO 4 was used for subsequent work.…”
Section: Selection Of Acid Medium and Optimization Of Concentrationmentioning
confidence: 98%
“…The effect of KMnO 4 concentration upon the CL intensity was examined in the range 0.025-0.35 mmol/L. The results showed that the signal/blank ratio of CL emission reached a maximum value when the concentration of KMnO 4 was 0.05 mmol/L, and higher concentrations of KMnO 4 resulted in a decrease of the CL emission intensity, owing to the KMnO 4 absorbing the emitted light (26,27). Therefore, 0.05 mmol/L KMnO 4 was used for subsequent work.…”
Section: Selection Of Acid Medium and Optimization Of Concentrationmentioning
confidence: 98%
“…Recently, Hindson and Barnett reported a comprehensive and critical review on the wide range of analytical applications of KMnO 4 in CL reactions [12]. The nature of these reactions has been postulated to involve the following excited state intermediates: manganese (II) or a complex [4,13,14,15], singlet oxygen [16,17], sulfur dioxide [1,18], molecular nitrogen [19,20], and fluorescent oxidation products of the analyte [21]. Meixner and Jaeschke proposed the following mechanism to explain the CL reaction of sulfite with permanganate [22]:…”
Section: Introductionmentioning
confidence: 98%
“…It appears that the optimization conditions and the CL signal are much dependent on the system configuration as well as type of acid used. [36][37][38][39][40] Hence, the signal intensity of 20 μM pyrogallol was used for normalization of other signals. The optimization of the 3-step CL COD method system was carried out.…”
Section: The Optimization Conditions For 3-step CL Cod Methodsmentioning
confidence: 99%